2013
DOI: 10.1016/j.nicl.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state functional connectivity as a marker of disease progression in Parkinson's disease: A longitudinal MEG study

Abstract: The assessment of resting-state functional connectivity has become an important tool in studying brain disease mechanisms. Here we use magnetoencephalography to longitudinally evaluate functional connectivity changes in relation to clinical measures of disease progression in Parkinson's disease (PD).Using a source-space based approach with detailed anatomical mapping, functional connectivity was assessed for temporal, prefrontal and high order sensory association areas known to show neuropathological changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 47 publications
11
86
2
Order By: Relevance
“…For each brain voxel (or ROI), we then averaged its normalized ΔFC with all other brain voxels (or ROIs), and this averaged normalized ΔFC was used as a measure of information exchange loss/gain for this voxel (or ROI) (Olde Dubbelink et al 2013). Figure 5 shows voxel-wise histograms (A) and spatial distributions (B) of the averaged normalized ΔFC for all isoflurane doses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each brain voxel (or ROI), we then averaged its normalized ΔFC with all other brain voxels (or ROIs), and this averaged normalized ΔFC was used as a measure of information exchange loss/gain for this voxel (or ROI) (Olde Dubbelink et al 2013). Figure 5 shows voxel-wise histograms (A) and spatial distributions (B) of the averaged normalized ΔFC for all isoflurane doses.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ΔFC at each dose was divided by the corresponding FC strength at the awake state (referred to as normalized ΔFC hereafter). Furthermore, to examine the change of information exchange for a local brain region (a voxel or ROI), we averaged the normalized ΔFC between this voxel (or ROI) and all other brain voxels (or ROIs) at each anesthetized condition (Olde Dubbelink et al 2013). This averaged normalized ΔFC was used as the quantity to measure information exchange loss/gain for the voxel/ROI.…”
Section: Methodsmentioning
confidence: 99%
“…MEG has been used to study cortico-muscular coherence (Airaksinen et al, 2015) and predict dementia in PD (Olde Dubbelink et al, 2014b). MEG has also been used to study functional connectivity alterations in PD (Olde Dubbelink et al, 2013, 2014a; Ponsen et al, 2013). …”
Section: Neuroimaging Methodsmentioning
confidence: 99%
“…23 The MEG study involved an earlier phase of the disease, i.e., the 4-year period preceding the 3-year follow-up period of the present fMRI study. The changes in MEG-derived functional connectivity were correlated with motor and cognitive deterioration.…”
Section: Relation Between Functional Connectivity and Clinicalmentioning
confidence: 99%
“…23,24 Apparently, increased synchronization might only take place in early disease stages, possibly serving as a compensatory mechanism in order to maintain normal functionality. Previous MEG studies have revealed increases in functional connectivity in PD, in particular at early disease stages.…”
Section: Relation Between Functional Connectivity and Clinicalmentioning
confidence: 99%